COMPOUNDING IN CENTRAL MANGGARAI DIALECT, MANGGARAI LANGUAGE, FLORES, INDONESIA - DIMAN, MARIA; TANS, FELIKS; OTTA, GRACIA M. N. (Academic Journal of Educational Sciences, 2022)
This research is conducted to answer how compounds in the dialect are formed. At the end of this research, it shows some educational implications. The research method used was descriptive qualitative in which data collection methods used were observations, interviews, and documentary studies. The informants interviewed were native speakers from Ngeri village and the documents studied have been taken from some textbooks written in Central Manggarai dialect. It was found that there are seven kinds of compounds in Central Manggarai Dialect formed by combining two words with different meanings and different classes, namely: 1) noun and noun compounding; 2) noun and adjective compounding; 3) noun and verb compounding; 4) noun and adverb compounding; 5) verb and noun compounding; and, 6) verb and adjective compounding; and, 7) adjective and noun compounding. For Manggaraian children learning such languages as Indonesian and English, it is important that when teaching those languages, their teachers teach those forms of compounding and their meanings by comparing how they are formed in Manggarai language to how they are formed in such languages as Indonesian and English and by explicitly teaching what their meanings are. By relying on their understanding of such forms and meanings of compounding in Manggarai language, it is hoped that they can understand how such forms of compounding are also formed in other languages.